x+(x-35)+(2x+39)=604

Simple and best practice solution for x+(x-35)+(2x+39)=604 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x+(x-35)+(2x+39)=604 equation:


Simplifying
x + (x + -35) + (2x + 39) = 604

Reorder the terms:
x + (-35 + x) + (2x + 39) = 604

Remove parenthesis around (-35 + x)
x + -35 + x + (2x + 39) = 604

Reorder the terms:
x + -35 + x + (39 + 2x) = 604

Remove parenthesis around (39 + 2x)
x + -35 + x + 39 + 2x = 604

Reorder the terms:
-35 + 39 + x + x + 2x = 604

Combine like terms: -35 + 39 = 4
4 + x + x + 2x = 604

Combine like terms: x + x = 2x
4 + 2x + 2x = 604

Combine like terms: 2x + 2x = 4x
4 + 4x = 604

Solving
4 + 4x = 604

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4' to each side of the equation.
4 + -4 + 4x = 604 + -4

Combine like terms: 4 + -4 = 0
0 + 4x = 604 + -4
4x = 604 + -4

Combine like terms: 604 + -4 = 600
4x = 600

Divide each side by '4'.
x = 150

Simplifying
x = 150

See similar equations:

| 5+y=500 | | (B-4)(b^2+3b-2)= | | 0.50x+0.75(10)=0.25(44) | | 3y-14=46 | | 6n-1-10n=51 | | 4x+3-2x+5= | | 2d^3-7d^2+6d=0 | | 11x-26=106 | | -k=3(k-8) | | (3x-4)(3x-4)= | | 2d^3-7d+6d=0 | | -2y+12=-2(2y+1) | | (2x+4)(2x-4)= | | -35=7(a-8) | | x^2+kx+12=0 | | 60x^2+100x+40=0 | | x^2+7=9x | | -9x+41=131 | | 3x+4x-10=60 | | 6z=78 | | 6t-18= | | 32h-16=8(2h-10) | | x-22=-9 | | 4t^2-12t+9= | | 16K^2-6K+6=0 | | -18+x=9 | | 4y^2+5y+1=0 | | 1+4x+x^2=0 | | -10x-99=71 | | 4b+7=-9 | | 4y+7=2-y | | 8(3+a)=64 |

Equations solver categories